Long-Term Results of Cryosurgery and Combined Treatment of Patients With Deep Brain Tumors - Kaliuzhka, Vladyslav; Piatykop, Volodymyr; Cherniaieva, Oleksandra (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):294